Heterogeneous effect of uncertainty on corporate investment: Evidence from listed firms in the Republic of Korea - Cheonkoo Kim; Jungsoo Park; Donghyun Park; Shu Tian (Asian Development Bank (ADB), 2022)
In this paper, we analyze the effect of financial uncertainty on corporate investment using firm-level panel data from the Republic of Korea. We find that financial uncertainty has a significant negative effect on corporate investment, and that the effect is heterogeneous across firms of different sizes. Small firms and large firms are more exposed to the negative effect of uncertainty than are mediumsized firms. The negative effect of uncertainty on large firms slightly declined after the global financial crisis, but it increased for small and medium-sized enterprises (SMEs). Financial constraints and investment irreversibility amplify the negative effect of uncertainty. The inverted U-shaped curve of the uncertainty effect along the firm-size spectrum can be understood as follows: Small firms are more financially constrained and large firms' investments are more irreversible in nature. Lastly, contrary to widespread belief, uncertainty has waned since 1990, dampening the trend of declining investment ratios. To counter the negative effect of uncertainty on SMEs, policies need to be directed toward the development of capital markets and bond markets for SMEs. Furthermore, SME policies should be redirected to target competitiveness, not protection.
Keywords: E22; G31; 330; uncertainty; corporate investment; financial constraints; investment irreversibility